Management and cleanup of legacy radium-contaminated sites in the United States. (24th August 2021) - Grossman, C; Barr, C; King, D; McKenney, C; Koenick, S; Chang, R
Abstract: The hazards associated with radium-containing materials were largely unknown when they were first introduced into household and other products over a century ago. Radium was also originally thought to have beneficial health properties, leading to confusion amongst the public about the safety of radium in household products and food items. When the adverse health effects associated with radium were discovered and became well known, radium products became unpopular and were prohibited in some countries. In the United States, after the hazards associated with radium became known, radium was first regulated by individual states in the late 1920s and early 1930s. Later, the US Nuclear Regulatory Commission (NRC) was given a role in the regulation of discrete sources of radium with the passage of the Energy Policy Act of 2005. After passage of the Act, the NRC began to systematically identify sites around the country where radium was used and reached out to site owners to determine whether existing radium contamination could pose a risk to public health and safety and the environment. The NRC devised a graded approach in response to its new regulatory responsibilities to address potential public health and safety issues at legacy radium sites. By September 2019, the NRC had dispositioned all the sites that were identified as having potential contamination from historical radium within its regulatory purview in non-Agreement States. The staff worked with site owners and federal, state and local officials, as needed, to properly disposition the sites to ensure that each site either meets the applicable criteria for unrestricted use or has controls in place to limit access during remediation so that no site poses an unacceptable risk to public health and safety and the environment.